KECEMASAN REMAJA PUTRI DALAM MENGHADAPI MENARCHE - Ridwan, Ahmad; Probo, Agistya (Jurnal AKP, 2014)
Teens are individuals, both women and men who are in a period or age between children and adults, one mark of a young woman who went through the menarche. Menarche that arise can lead to anxiety. The purpose of this study was to describe the level of anxiety in the face of menarche girls in SDN Ketawang 02 Purwoasri.        The research design used in this study is descriptive, population samples of  35 students and the class V / VI by 35 respondents. Sampling technique using total sampling. Data were collected by using a scale koesioner Hars.              The results showed that most of the 25 men (71.5%) experienced moderate anxiety, and 10 people (28.5%) experienced mild anxiety.       From the research, most of the respondents experienced moderate levels of anxiety, hence the need for education about menarche and reproductive health consultations to add information and knowledge so as to reduce anxiety. Key words : Anxiety, Teens, menarche.